The modernization of Chinese literature in Malaysia: A case study of the poets community of Jiao Feng (1955-1959) - Ng, Y.L.; Fan, P.S.; Ding, S.L. (2010)
Modern Malaysian Chinese poems originated in the early 1950s. Wen Zichuan, Wei Beihua and Bai Ya were all initiators of modern Malaysian Chinese poems. Since the publication in November 1955 of the inaugural issue of Jiao Feng, which stood at the forefront of modern Chinese poems, a large volume of contemporary poems have been continuously published. The style and language of these poems exhibited the poets' attempt to break through the simple and unadorned style of realistic poems and indicated the development of modern Malaysian Chinese poems. From the publication of the inaugural issue of Jiao Feng to the publication of the first revised edition (78th issue) in April 1959, this five-year period was seen as the early formation period of the groups of poets for Malaysian Chinese magazines. In the 1950s, Malaya was preparing itself to free from British colonization and to achieve independence. In such a social background, Malaysian Chinese poems exhibited unique features. This paper is an attempt to analyze the influence of post-war external influence on modern Malaysian Chinese poems through examining the works of modern Malaysian Chinese poets.